The Impact of Active Learning Strategies on Social Studies Achievement among Third-Grade Intermediate Students (Clustered Learning as a Model) - Hadi, Malik Ghazi (Journal of Research in Innovative Teaching and Inclusive Learning, 2026)
In this research, we focused on the cluster learning model to examine the effect of the active learning strategy on social studies achievement among third-grade intermediate students. The study used an experimental design of two groups (experimental and control). (A sample of third-year intermediate students was chosen and divided into two groups: an experimental group of 28 who studied using the cluster learning strategy, and a control group of 28 who studied using the traditional method. The validity and reliability of the research instrument, which consists of an objective achievement test, remain to be confirmed. The results also indicated statistically significant differences in the experimental group, favoring the display and clustering of historical and geographical information, corroborating our understanding from the experiments. This results in improved educational achievement and the development of organized thinking skills among students. The importance of social studies (geography in particular) lies in its role as one of the basic pillars for building national and cognitive awareness among intermediate school students. It seeks to engage students with the geography where they live and its deep history, and to help them learn about the nuanced interactions between people and place. In more detail, as educational theories have evolved across various levels, the trend has shifted from traditional, lecture- and rote-memorization-based instruction to active learning models focused on learner-centered approaches. From a teaching method perspective, this is where the cluster learning strategy comes into play as the connecting visual and cognitive tool that can structure geographical knowledge; it has turned scattered knowledge into an interlinked hierarchical network of concepts. Geography: The profound impact of this strategy on the academic achievement of third-grade middle school students, based on sound methodological and experimental foundations.